2008
DOI: 10.1253/circj.cj-08-0072
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Exogenous Tetrahydrobiopterin on Left Ventricular Remodeling After Myocardial Infarction in Rats The Possible Role of Oxidative Stress Caused by Uncoupled Endothelial Nitric Oxide Synthase

Abstract: eleterious left ventricular (LV) remodeling after myocardial infarction (MI) is the major cause of heart failure. Although therapeutic strategies designed to limit ventricular remodeling after MI can decrease the incidence of congestive heart failure and improve survival, 1 mechanisms of remodeling process remain not fully elucidated. At the cellular level, reactive oxygen species (ROS) and oxidative stress play a key role in regulating myocardial remodeling. 2,3 In the stressed heart, there is an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
1
38
1
Order By: Relevance
“…BH 4 is highly sensitive to oxidation and, with BH 4 deficiency, oxygen reduction uncouples from NO synthesis, thereby converting eNOS into a superoxide-producing enzyme. 40 In our ex vivo experiments on vessels from patients with HD, exposure to exogenous BH 4 or to resveratrol restored eNOS functionality and, hence, reduced oxidative stress.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…BH 4 is highly sensitive to oxidation and, with BH 4 deficiency, oxygen reduction uncouples from NO synthesis, thereby converting eNOS into a superoxide-producing enzyme. 40 In our ex vivo experiments on vessels from patients with HD, exposure to exogenous BH 4 or to resveratrol restored eNOS functionality and, hence, reduced oxidative stress.…”
Section: Discussionmentioning
confidence: 68%
“…BH 4 is highly sensitive to oxidation and, with BH 4 deficiency, oxygen reduction uncouples from NO synthesis, thereby converting eNOS into a superoxide-producing enzyme. 40 In our ex vivo experiments on vessels from patients with HD, exposure to exogenous BH 4 or to resveratrol restored eNOS functionality and, hence, reduced oxidative stress.The action we observed on NO occurs through an AMPKdependent mechanism. It was recently proposed that misregulation of AMPK is involved in the metabolic defects underlying progression to dysmetabolic syndrome.…”
mentioning
confidence: 68%
“…[23][24][25][26] Although the increase in reparative fibrosis and ECM serves to preserve the structural integrity of infarcted tissue in the early phase of MI, in the chronic phase, the accumulation of a large amount of fibrosis, especially interstitial fibrosis, leads to ventricular diastolic dysfunction rather than preservation of cardiac structure. [27][28][29][30] In our rat model of MI, heart function continued to deteriorate 4-8 weeks after MI in the MI group, while the injection of MMP-1 plasmid DNA significantly improved heart function.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Our recent studies have shown that myocardial oxidative stress is enhanced in the initial development of LV dysfunction in TO-2 hamsters. [12][13][14] In the present study, we demonstrated that the GSH/GSSG ratio was decreased in the failing heart of untreated TO-2 hamsters compared with F1B control hamsters at 12 weeks of age.…”
Section: Effects Of Ghrp-2 On Myocardial Oxidative Stress and Antioximentioning
confidence: 99%